The gap between public and private wages: new evidence for the EU - de Castro, Francisco; Salto, Matteo; Steiner, Hugo (Luxembourg, 2013)
"This paper aims to assess the size of the wage gap between the public and private sectors within all European Union countries by using the European Structure of Earnings Survey (SES henceforth), compiled by Eurostat for the years 2006 and 2010. Public sector employees are found to enjoy on average higher wages than comparable workers in the private sector in 2010, even after controlling for the level of educational attainment. Regarding gender, contrary to other empirical papers, for the countries with full public sector coverage, we do not find evidence of a higher positive wage gap for women. On average the public wage premium is higher for older workers and workers with lower levels of education. Finally, negative public wage premia are found for workers at higher positions, whereas the positive and sometimes large overall public wage gaps are mainly explained by the sizeable gaps observed at lower job positions."